2022
DOI: 10.3389/fmed.2022.983259
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of the inflammatory response: The next step in personalized medicine after severe trauma

Abstract: Infections in trauma patients are an increasing and substantial cause of morbidity, contributing to a mortality rate of 5–8% after trauma. With increased early survival rates, up to 30–50% of multitrauma patients develop an infectious complication. Trauma leads to a complex inflammatory cascade, in which neutrophils play a key role. Understanding the functions and characteristics of these cells is important for the understanding of their involvement in the development of infectious complications. Recently, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…As it is now possible to measure the neutrophil functional phenotype at any time point after trauma, the longitudinal course of the inflammatory response and the impact of additional interventions can be followed. In the future, measuring the neutrophil compartment over time could possibly guide decision making regarding timing and extent of immune protective surgery and determine the administration of (preventive) antibiotics [22]. Second, our results showed that patients in Categories 0-2 had similarly low injury severity scores.…”
Section: Discussionmentioning
confidence: 71%
“…As it is now possible to measure the neutrophil functional phenotype at any time point after trauma, the longitudinal course of the inflammatory response and the impact of additional interventions can be followed. In the future, measuring the neutrophil compartment over time could possibly guide decision making regarding timing and extent of immune protective surgery and determine the administration of (preventive) antibiotics [22]. Second, our results showed that patients in Categories 0-2 had similarly low injury severity scores.…”
Section: Discussionmentioning
confidence: 71%